Identifikasi Kebutuhan Penanganan Jalan Berdasarkan Nilai IRI (International Roughness Index) dan PCI (Pavement Condition Index) - Sapta Santosa; Siegfried Siegfried; Bayu Kania (Publikasi Indonesia, 2022)
Identification of road handling needs is an activity of searching, collecting, researching, and recording data and information on road needs that emphasize the comfort factor in driving, where these factors can occur from road geometric conditions, unevenness or hardness of the road surface. The identification of road handling needs that I will do in this research is a case study of national road conditions in the Sorong region of West Papua Province, which aims to provide input for the proposed road handling needs program for an area traversed by the national road network so as to achieve an optimal, effective and efficient road handling program. The data used in this analysis are IRI value data and PCI values, from these data can produce a road stability and road conditions, which will then be analyzed for the proposed handling needs program. The proposed national road handling needs program in the Sorong region, West Papua Province from the results of the analysis carried out on asphalt pavement there is 82.71% handling on the length of the road and there are 17.34% of the length of the road on the type of concrete pavement.